Peer Support and Self Efficacy Predict Student Engagement: Dukungan Teman Sebaya dan Efikasi Diri Memprediksi Keterlibatan Siswa - Muhammad hatta; Ghozali Rusyid Affandi (Academia Open, 2025)
General Background: Student engagement represents the quality and quantity of students’ cognitive, behavioral, and emotional involvement in learning processes and is closely associated with academic achievement. Specific Background: Low participation in classroom activities is linked to negative student behaviors and reduced academic and non-academic outcomes, making engagement an important concern in elementary education contexts. Knowledge Gap: Empirical studies examining the combined contribution of peer support and self-efficacy toward engagement among Indonesian elementary school students remain limited, particularly using simultaneous statistical analysis. Aims: This study aimed to examine the role of peer support and self-efficacy in relation to student engagement among students at State Elementary School Suko 2 Sidoarjo. Results: A quantitative correlational design was applied to 195 students selected through stratified random sampling from a population of 590 students. Data collected using peer support, self-efficacy, and student engagement scales were analyzed through multiple linear regression with SPSS version 29. The analysis indicated that peer support and self-efficacy simultaneously showed a significant relationship with student engagement (F=69.734, p=0.001). Partial testing also demonstrated significant relationships for peer support (p<0.001) and self-efficacy (p<0.001). Novelty: The study provides integrated statistical evidence demonstrating the simultaneous contribution of social and psychological variables to learning engagement within an elementary school setting. Implications: The findings highlight the importance of strengthening supportive peer environments and students’ confidence in learning abilities to foster active participation in educational processes. Highlights: Social Encouragement Among Classmates Is Significantly Associated With Higher Classroom Involvement. Strong Personal Confidence in Learning Abilities Corresponds With Greater Participation in Academic Activities. Combined Psychosocial Variables Show Statistically Significant Relationships Based on Regression Analysis Results. Keywords: Peer Support, Self-Efficacy, Student Engagement, Elementary Education, Learning Participation